AB0423 Minimally invasive surgical treatment of temporomandibular joint in patients with various rheumatic disorders. (15th June 2017) - Zaslavskiy, I; Drobyshev, A; Dubinina, T; Erdes, S; Kuznetsov, A
Abstract : Background: Currently, maxillofacial surgery to actively develop and improve minimally invasive surgical methods for the treatment of patients with diseases of temporomandibular joint (TMJ). These types of surgical treatments like arthroscopy and artrolavazh TMJ are less traumatic and therefore can be effective in patients with rheumatic pathology. Objectives: To evaluate the efficacy of minimally invasive surgical treatment of TMJ in patients with rheumatic diseases (RD). Methods: In the study were included 64 pts aged from 18 to 65 years with various rheumatic disorders and lesions of the TMJ. Of these, rheumatoid arthritis (RA) - 43 (67.2%), psoriatic arthritis (PsA) 11 (17.2%), systemic lupus erythematosus - 8 (12.5%) and ankylosing spondylitis (AS) - 2 (3.1%). Before and after 14 days, a month and 6 months after surgery were assessed the following parameters: the level of pain in the TMJ (VAS), the aperture of mouth opening. All the patients at baseline and at 6 months after treatment was performed MRI of the TMJ. Interpretation of the TMJ MRI studies performed by the presence of signs of pathological changes in the joint, which were scored according to the number of pathological signs (from 0 to 8 points). As a preparatory stage before surgery all patients – splint therapy during 1 month was performed. Surgery included arthrolavage and arthroscopy TMJ followed by the introduction of hyaluronic acid. Results: Before treatment all patients had severe involvement of the TMJ by Wilkes international classification: III of St is 62.5%, IV – by 21.9%, V – 15, 6%. 6 months after surgical treatment the level of pain in the TMJ decreased 9.8 times (from 4.9 to 0.5, p<0, 0001). Mouth opening increased 2.3 times (from 17.5 mm to 40.9 mm, p<0, 0001), was reached from 96.7% of patients normal value. In the control MRI study of the TMJ at 6 months after surgery, the quantity of signs of pathological changes in the joints were reduced by 2.7 times in comparison with the initial level. The best results were achieved in patients with RA and PsA. The lowest result was achieved in the group of patients with AS. Conclusions: Minimally invasive methods of surgical treatment of TMJ (arthrolavage and arthroscopy), the most effective and appropriate for the treatment of patients with RD lesion of the temporomandibular joint. Disclosure of Interest: None declared